Cartographie des thèses portant sur l’éducation, l’enseignement et la formation dans les pays francophones du Sud de 2000 à 2020 - Jean-Pierre Chevalier (Éducation et Socialisation)
The directory of theses that can be consulted on the APPRENDRE website of the Agence Universitaire de la Francophonie lists theses in French about education, teaching and training in 26 countries in Africa, Indian Ocean plus Lebanon and Haiti. This directory was updated in early 2022. It lists 1816 theses defended from 2000 to 2020. Quantitative analysis highlights centers of doctoral research : in Algeria, Côte d’Ivoire, Morocco and Senegal... The qualitative approach makes it possible to identify the themes favored by researchers about education, teaching and training, or in the management of education systems. Finally, the chronological approach highlights the growth in Africa of French-speaking research in education.